High‐voltage gain zero‐current switching push–pull resonant converter for small energy sources. Issue 4 (1st March 2016) - Bilsalam, Anusak; Boonyaroonate, Itsda; Chunkag, Viboon
Abstract : This study presents a high‐voltage gain zero‐current switching (ZCS) push–pull resonant converter for small energy sources. The converter provides a high voltage from a 12 V DC battery via isolated transformer and full‐bridge rectifier. The main switches of the push–pull and full‐bridge diode rectifier operate under ZCS condition. The advantage of this technique is the use of leakage inductance for ZCS operation of the power switch and in designing the secondary side of a resonant tank. A prototype high‐voltage gain push–pull resonant converter was built and operated at 110 kHz fixed switching frequency, 350 V DC output voltage, and 200 W output power to analyse the effect of parasitic junction capacitance of the full‐bridge rectifier, which significantly affects the operating point of the resonant tank and the voltage. This study introduces the implementation and design using the data of a single diode to calculate the parameters. The simulation and experimental results verified the proposed and designed circuits. Both results agreed with the theoretical analysis.